Capacitors: A High‐Performance Lithium‐Ion Capacitor Based on 2D Nanosheet Materials (Small 6/2017). Issue 6 (February 2017) - Li, Shaohui; Chen, Jingwei; Cui, Mengqi; Cai, Guofa; Wang, Jiangxin; Cui, Peng; Gong, Xuefei; Lee, Pooi See
Abstract : A high‐performance lithium‐ion capacitors (LIC) based on two dimensional nanosheet materials, made of ZnMn2 O4 ‐graphene (ZMO‐G) hybrid nanosheets anode and N‐doped carbon nanosheets (NCN) cathode is realized by P. S. Lee and co‐workers in article number 1602893. The fabricated LIC delivers a high specific energy of 202.8 Wh kg −1 at a power of 180 W kg −1, the specific energy can still remain 98 Wh kg −1 even when the power density reaches as high as 21 kW kg −1 .